Increased expression of CD40/TRAF1 and activation of nuclear factor-κκB-dependent proinflammatory gene expression in collagen-induced arthritis. (2nd November 2018) - Cheng, T; Wang, M; Chen, L; Guo, Y; Chen, Z; Wu, J
Abstract : Objective : Genetic studies have implicated both CD40 and tumour necrosis factor receptor-associated factor-1 (TRAF1) with rheumatoid arthritis (RA). CD40 signalling is known to be associated with TRAF1 expression, directly or indirectly; however, the detailed mechanisms of these interactions are not clear in RA, and in particular in fibroblast-like synoviocytes. This study aims to investigate this pathway and the role of nuclear factor-κB (NF-κB) in a mouse model of RA. Method : We utilized the collagen-induced arthritis (CIA) model in DBA/1 mice. CD40, TRAF1, and NF-κB p65 were quantitated by enzyme-linked immunosorbent assay and immunohistochemistry in serum and tissue, respectively. Real-time polymerase chain reaction was applied to measure NF-κB-related gene expression, including cytokines [tumour necrosis factor-α (TNF-α), interleukin-6 (IL-6)] and adhesion molecules [intercellular adhesion molecule-1 (ICAM-1), vascular adhesion molecule-1 (VCAM-1)]. Results : The severity of arthritis by clinical and histological assessments peaked on day 35 and decreased thereafter. Serum levels of CD40, TRAF1, and NF-κB p65 paralleled this time-course. The tissue expression of the CD40, TRAF1, total NF-κB p65, and phospho-NF-κB p65 proteins, as well as NF-κB-related gene expression, including cytokines (TNFα, IL-6) and adhesion molecules (ICAM-1, VCAM-1), were markedly upregulated within 25–50 days after CIA. Conclusion : Our data identify a cellular/molecular mechanism of the CD40/TRAF1 signalling pathway involved in CIA: increased expression of CD40 and its adaptor TRAF1 proteins and activation of the NF-κB-dependent proinflammatory pathway. These correlations implicate possible mechanistic pathways in this model that may also operate in human RA and thus provide rationales for new therapeutic modalities.